2007
DOI: 10.1093/eurheartj/ehm401
|View full text |Cite
|
Sign up to set email alerts
|

A pathophysiologic study of tako-tsubo cardiomyopathy with F-18 fluorodeoxyglucose positron emission tomography

Abstract: The extent of metabolic defect involving apical akinetic area was more severe than perfusion abnormality. Our data suggest that sudden emotional or physical stress may cause a catecholamine-induced metabolic disorder in the myocardium, which is probably central to this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 41 publications
8
118
0
1
Order By: Relevance
“…Other authors demonstrated, in patients with TS, abnormalities of the microcirculation through myocardial perfusion scintigraphy with technetium 99 m tetrofosmin (20)(21)(22). A disorder of glucose and fatty acid metabolism, even more, severe of the perfusion defect, has also been demonstrated (23)(24). Abnormalities of coronary microcirculation have been also detected using contrast echocardiography (25)(26).…”
Section: Discussionmentioning
confidence: 93%
“…Other authors demonstrated, in patients with TS, abnormalities of the microcirculation through myocardial perfusion scintigraphy with technetium 99 m tetrofosmin (20)(21)(22). A disorder of glucose and fatty acid metabolism, even more, severe of the perfusion defect, has also been demonstrated (23)(24). Abnormalities of coronary microcirculation have been also detected using contrast echocardiography (25)(26).…”
Section: Discussionmentioning
confidence: 93%
“…Studies measuring myocardial perfusion via TIMI myocardial perfusion grade (TMPG) as well as nuclear imaging have demonstrated coronary microcirculatory disturbances. [9,10] It has been hypothesized that these microvascular abnormalities may result from increased mechanical wall stress as a consequence of apical ballooning. [11] Nonetheless, these abnormalities may manifest as abnormal nuclear stress tests, as in our case, and stress tests should be interpreted with caution in patients with stress cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is coronary microvascular dysfunction [12] . Impaired microvascular function and myocardial metabolic disturbances have been found in patients with TS on basis of thallium-201 and 18 F-fluorodeoxyglucose myocardial scans [13] .…”
Section: Discussionmentioning
confidence: 99%